2023
DOI: 10.1002/chem.202300680
|View full text |Cite
|
Sign up to set email alerts
|

Bis[1]benzothieno[1,4]thiaborins as a Platform for BODIPY Singlet Oxygen Photosensitizers

Abstract: A synthetic approach to two regioisomeric πelectron extended [1,4]thiaborins annulated with two benzothiophene units has been developed. The central thiaborin rings of the boracycles obtained exhibit different electronic properties; this is reflected in their different aromatic characters, boron Lewis acidity and UV-vis spectroscopic behavior. Thiaborins were converted to boron dipyrromethene (BODIPY) complexes. Their emission spectra exhibit two distinct bands resulting from 1 LE and 1 CT transitions. Strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…5 ), mainly through mutual interactions between ligands (3c and 3d) or alternating ligand-borafluorene moiety stacking (3f). Notably, J-aggregate motifs, commonly encountered in spiro-organoboron compounds, 13 are solely observed for 3e (Fig. S2.4, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
“…5 ), mainly through mutual interactions between ligands (3c and 3d) or alternating ligand-borafluorene moiety stacking (3f). Notably, J-aggregate motifs, commonly encountered in spiro-organoboron compounds, 13 are solely observed for 3e (Fig. S2.4, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
“…Thiophene-fused thiaborin (DTSB) compounds, which are hybrid building blocks of boron and sulfur, have also been reported . We have shown that polymers based on the F DTSB unit exhibit strong intermolecular interactions in the solid state, which are relatively rare for p-π* conjugated systems because triarylboranes require large steric groups on boron to prevent hydrolysis and oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…5,22–24 Thiophene groups were included in the structure due to their advantages such as absorption ability in the visible region, moderate band gap, and promotion of intersystem crossing. 25,26 In this context, three new cyclotriphosphazene derivatives were synthesized, and their molecular structures were characterized (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%